2022
DOI: 10.1038/s41419-022-05459-4
|View full text |Cite
|
Sign up to set email alerts
|

The divergent effects of astrocyte ceruloplasmin on learning and memory function in young and old mice

Abstract: Ceruloplasmin (CP) plays an important role in maintaining iron homeostasis. Cp gene knockout (Cp-/-) mice develop a neurodegenerative disease with aging and show iron accumulation in the brain. However, iron deficiency has also been observed in 3 M Cp-/- mice. The use of systemic Cp gene knockout is insufficient to reveal specific functions for CP in the central nervous system. Considering recent discoveries that astrocytes synthetize the majority of brain CP, we generated astrocyte conditional Cp knockout (Cp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 74 publications
2
13
0
Order By: Relevance
“…Thus, aged Cp cKO animals exhibit alterations of executive‐level processes, such as short‐term memory. In agreement with our results, Li et al (2022) have recently shown that Cp deletion in GFAP‐positive astrocytes induces learning and memory deficits, reductions in synapse density, and abnormal hippocampal neurogenesis in adult mice. However, they found improved learning and memory functions and reduced brain iron levels in aged Cp‐deficient animals (Li et al, 2022).…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…Thus, aged Cp cKO animals exhibit alterations of executive‐level processes, such as short‐term memory. In agreement with our results, Li et al (2022) have recently shown that Cp deletion in GFAP‐positive astrocytes induces learning and memory deficits, reductions in synapse density, and abnormal hippocampal neurogenesis in adult mice. However, they found improved learning and memory functions and reduced brain iron levels in aged Cp‐deficient animals (Li et al, 2022).…”
Section: Discussionsupporting
confidence: 94%
“…In agreement with our results, Li et al (2022) have recently shown that Cp deletion in GFAP‐positive astrocytes induces learning and memory deficits, reductions in synapse density, and abnormal hippocampal neurogenesis in adult mice. However, they found improved learning and memory functions and reduced brain iron levels in aged Cp‐deficient animals (Li et al, 2022). In our experiments, Cp deletion was induced at specific time‐points and was restricted to only Glast1‐positive astrocytes of the postnatal brain (Cheli et al, 2021; Tran et al, 2018).…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Both Cp and Heph are homologous ferroxidases that aid Fpn in the export of iron from cells, with Heph most commonly found in barrier cells such as ECs (Jiang et al, 2015). Cp is in a glycosylphosphatidylinositol‐anchored form present in astrocytes (Patel & David, 1997) but still vital to brain iron acquisition (Li et al, 2022). Soluble Cp has been implicated in the stimulation of iron release from ECs (McCarthy & Kosman, 2014; Patel et al, 2002).…”
Section: Regulation In Homeostasismentioning
confidence: 99%
“…Further research has expounded that astrocytes are essential for iron homeostasis regulation in neurons. Moreover, iron content in astrocytes and microglia is reported to increase with age …”
Section: Ferroptosis In Neurodegenerative Diseasesmentioning
confidence: 99%